Girls’ ‘pain memes’ on youtube: The production of pain and femininity on a digital network - Dobson, Amy (2015)
In this chapter, the author tentatively calling pain meme' videos on You Tube created by teenage girls in Australia and other Western countries. The author use the phrase pain meme' to describe a particular style of video blog found on You Tube, and seemingly created mostly by young women, who use handwritten flash-cards and an emotive music soundtrack to narrate personal experiences of bullying, abuse, grief, and often also self-harm, eating disorders and anxiety. The videos related to Todd's that surface on You Tube have several stylistic features in common: the use of handwritten flash-cards to tell a story while the subject remains silent; a black and white film setting; and an emo' ballad soundtrack. Many such videos predate Todd's. Research conducted on the representation and discussion of self-harm and suicide online is of some use in helping us understand the meaning and function of pain meme videos.